2018
DOI: 10.1002/pc.24772
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardant and thermal decomposition mechanism of poly(butylene terephthalate)/DOPO‐HQ composites

Abstract: Poly(butylene terephthalate) (PBT)/10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) composites with poly(ethylene-butylacrylate-glycidylmethacrylate) (PTW) as a compatibilizer were prepared by the twin-screw extruder. The flame retardant and thermal decomposition mechanism of the PBT/DOPO-HQ flame retardant composites was investigated. The limiting oxygen index (LOI), vertical burning test (UL94), cone calorimetric test, thermogravimetric analysis, laser micro-Raman spectrometer (LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…He et al . reported a drastic reduction in tensile strength and Izod impact strength when PBT was added with commercial FR 10-(2, 5-dihydroxyl phenyl)-9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) 49 . They found that the DOPO-HQ required 15 wt% in the PBT in order to achieve V-2 fire class and 20 wt% to reach V-0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al . reported a drastic reduction in tensile strength and Izod impact strength when PBT was added with commercial FR 10-(2, 5-dihydroxyl phenyl)-9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) 49 . They found that the DOPO-HQ required 15 wt% in the PBT in order to achieve V-2 fire class and 20 wt% to reach V-0.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the DOPO-HQ required 15 wt% in the PBT in order to achieve V-2 fire class and 20 wt% to reach V-0. The tensile strength of PBT reduced ~39% from 56.9 to 34.2 MPa with the addition of 20 wt% DOPO-HQ 49 . This study’s biobased FR required only 7.5 wt% to be effective and showed only a ~13% reduction in tensile strength, which is superior to commercial phosphorus-based FRs in the market in terms of mechanical properties retention.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining N content in the TAD6EG6 was 0.14% N per 1% TAD, which is slightly lower than that of TAD12 (0.16% N per 1% TAD). According to the previous research work [24,29,37,38], the flame-retardant effect of TAD was due to its decomposition products during combustion: (i) P-containing free radicals which can quench the free radicals from degraded resin matrix, and terminate the chain reaction in the gas phase, and (ii) incombustible N-containing gas which diluted the flammable gases released from the resin matrix. TAD acts weak in the condensed phase due to that most of the phosphorus is released to the gas phase, and only minor charring activity is remained [30].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the infrared spectra of the composites before and after combustion are shown in Figure 7B. After normalization, the peak at 2348 cm −1 corresponded to the CO 2 stretching vibration 17 . A new peak appeared at 1347 cm −1 that was attributed to the stretching vibration of the primary amide C–N generated after burning.…”
Section: Resultsmentioning
confidence: 99%